Analisis Perbandingan Profitabilitas Terhadap Nilai Perusahaan Sebelum Dan Selama Pandemi Covid-19 Pada Industri Makanan Dan Minuman Yang Terdaftar Di BEI - Haliza Hafiz; Vina Citra Mulyandani (Indonesian Accounting Literacy Journal, 2022)
This study aims to analyze the effect of profitability on company value before and during the covid-19 pandemic and compare profitability and company value before the covid-19 pandemic and during the covid-19 pandemic in food and beverage sector companies listed on the IDX for the period 2018-2021. The research method used is simple linear regression analysis and t test to analyze the effect of profitability on company value as well as paired sampled t test and Wilcoxon signed rank test for comparative analysis. The results of this study indicate that profitability has a positive effect on company value in the period before the covid-19 pandemic, and has a positive effect during the pandemic. Meanwhile, the comparative analysis shows that profitability has no difference before and during the covid-19 pandemic, but company value has differences before and during the covid-19 pandemic.